The Old Testament Background of Reconciliation in 2 Corinthians 5–7 and its Bearing on the Literary Problem of 2 Corinthians 6.14–7.1 - Beale, G. K. (New Testament studies, 1989)
Few scholars have proposed that there is any precise OT background for Paul's view of reconciliation, even though there has been much discussion about the formulation of the doctrine. There is no Hebrew word for ‘reconciliation’ in the OT; there is general agreement that Paul obtained this word from not only the Jewish but also the Greco-Roman world. The καταλλάσσω–διαλλάσσομαι word group is found in the Septuagint (rarely), 2 and 4 Maccabees and Josephus as well as in classical, hellenistic and koine writings. The use of the word group in these writings has been well documented.